Resolution of Glycerol, Ethanol and Methanol Employing a Voltammetric Electronic Tongue - de Oliveira, João Pedro Jenson [UNESP]; Bonet-San-Emeterio, Marta; de Sá, Acelino Cardoso; Cetó, Xavier; Paim, Leonardo Lataro [UNESP]; del Valle, Manel (MDPI, 2024)
This paper reports the use of nanoparticles (NPs)-modified voltammetric sensors for the rapid determination of glycerol in the presence of ethanol and methanol, which are used in the transesterification reaction of biodiesel production. Two different modified electrodes have been prepared to form the electronic tongue (ET): copper hexacyanoferrate NPs obtained by chemical synthesis and mixed into graphite/epoxy (GEC) electrode, and nickel hydroxide NPs electrodeposited in reduced graphene oxide onto a GEC electrode. The response characteristics of these electrodes were first evaluated by building the respective calibration against glycerol, ethanol, and methanol. The electrodes demonstrated good stability during their analytical characterization, while principal component analysis confirmed the differentiated response against the different alcohols. Finally, the quantification of mixtures of these substances was achieved by a genetic algorithm-artificial neural networks (GA-ANNs) model, showing satisfactory agreement between expected and obtained values.
Keywords: artificial neural networks; biodiesel; electronic tongue; glycerol; nanoparticles modifiers